Clinical profile assessment and sarcopenia on the final outcome of elderly hospitalized with COVID-19 (Research, Society and Development, 2022)
Objective: to evaluate the clinical profile and sarcopenia on the final outcome of elderly hospitalized with COVID-19. Methodology: observational, descriptive research with a quantitative approach. Held at the Infectioparasitic Diseases (IPD) COVID ward of a university hospital, João Pessoa - PB, from may to august 2021. For data collection, the following were used: an instrument developed by the researchers that contemplated sociodemographic, clinical and physical aspects; and measurement of Calf Circumference (CC) to assess appendicular mass loss. The sample consisted of 11 elderly people diagnosed with COVID-19. Results: the majority were male (63.6%), prevalence of comorbidities of 90.9% and sarcopenia indicative of 81.8%. It was possible to observe a significant relationship between CC and Body Mass Index (BMI) and comorbidities, all individuals who died had loss of appendicular mass and associated comorbidities. It was not possible to verify a relationship between CC and the final outcome. Conclusion: sarcopenia and COVID-19 have been identified as predictors of worse prognosis in the elderly population in general.